Feeding Tall Fescue Seed Reduces Ewe Milk Production, Lamb Birth Weight and Pre-Weaning Growth Rate - Britt, Jessica L. (Animals (Basel), 2020)
SIMPLE SUMMARY: This study was conducted to examine how ergovaline/ergovalinine ingestion during pregnancy in ewes with different DRD2 genotypes altered ewe and lamb performance. Feeding ergovaline/ergovalinine in last trimester reduced lamb birth weight; however, milk production was lower for all ewes fed ergovaline/ergovalinine. Lambs born to dams fed ergovaline/ergovalinine had slower growth rates and lower weaning weights. These results demonstrate that ingestion of ergot alkaloids during pregnancy can negatively influence lactation, growth of offspring and birth and weaning weights. Recommendations would include strategies to mitigate mycotoxin exposure in pregnant ewes to improve production. ABSTRACT: Endophyte-infected tall fescue (E+) produces ergovaline and ergovalinine, which are mycotoxins that act as dopamine agonists to suppress prolactin and induce vasoconstriction. The experiment was designed as a 3 × 2 × 2 factorial with DRD2 genotype (AA, AG, GG), fescue seed (endophyte-free, E− or endophyte-infected, E+), stage of gestation (MID, d (day) 35–85; LATE, d 86–parturition) and all interactions in the model. Pregnant Suffolk ewes (n = 60) were stratified by genotype and fed E+ or E− seed in a total mixed ration according to treatment assignment. Serum prolactin concentrations were lower (p < 0.05) in ewes fed E+ seed but did not differ by maternal DRD2 genotype or two-way interaction. Lamb birth weight was lower (p < 0.05) in ewes fed E+ seed in last trimester. Pre-weaning growth rate, milk production and total weaning weight was reduced (p < 0.05) in ewes fed E+ fescue seed during MID and LATE gestation. Ingestion of ergovaline/ergovalinine in last trimester reduces lamb birth weight; however, lamb growth rate, milk production and total weaning weight are reduced in all ewes fed E+ during mid and last trimester.